Analisis Produktivitas Kerja Perawat Ruang Rawat Inap Rumah Sakit Bina Kasih Kota Medan - Angela Christina; Arifah Devi Fitriani; Asyiah Simanjorang (Ilmu Bersama Center, 2022)
Productivity in nursing is closely related to the efficiency and effectiveness of nurses in providing nursing care. This study aims to analyze the work productivity of nurses in the inpatient room at Bina Kasih Hospital, Medan 2021. This study is a descriptive qualitative study. This research was conducted in the inpatient ward of Bina Kasih Hospital, Medan in October 2021. There were 10 informants in this study which included nurses and patients. The data were analyzed using an interactive model. Based on the results of the study, it was found that the productivity of nurses was still low, could not carry out their authority properly, so that patients complained a lot about the actions given by nurses. In addition to nurses doing nursing care, nurses also do work outside of that, namely cleaning, nurse stations, cleaning patient rooms. If the patient's complaint is classified as a mild complaint, the nurse immediately handles it, but if the complaint must involve management, the nurse makes a patient complaint report addressed to the supervisor. Nurses in the room have not been able to apply the nursing care process starting from the assessment stage to the evaluation stage. The nurse is still copying and pasting from the nurse's notes on the previous shift. nurses have applied smiles and greetings. Suggestions in this study are for nurses to be better in the future in order to improve the quality of Human Resources in the field of nursing as nursing service providers and public interest in seeking treatment at the Bina Kasih hospital.